Sinergitas Pustakawan dan Guru Dalam Meningkatkan Minat Baca Siswa di SMP Islam Al-Ulum Terpadu - Eka Putri Wildyani; Makmur Syukri (Dinasti Review, 2024)
This study aims to identify factors influencing students' reading interest, analyze efforts undertaken by librarians and teachers to promote reading, explore existing forms of synergy between librarians and teachers in fostering reading interest, and formulate effective synergistic strategies between librarians and teachers to enhance students' reading interest, particularly at SMP Islam Al-Ulum Terpadu. Employing a qualitative research methodology, the study involves field observation, interviews, in-depth analysis, and conclusion formulation presented in a narrative and written format. Findings reveal that a more comprehensive and structured strategy is still required to strengthen the synergy between librarians and teachers in promoting reading interest among students at SMP Islam Al-Ulum Terpadu Tuasan. By enhancing synergy or collaboration, enriching library collections, developing engaging literacy programs, and integrating technology into literacy initiatives, it is anticipated that students' reading interest will significantly improve. This, in turn, will support students' academic and personal development, preparing them to become lifelong learners in the information age.